Pengaruh Fasilitas dan Citra Destinasi Wisata Terhadap Peningkatan Kepuasan Wisatawan di Karst Tubing Sedayu - Brilliani, Aprillia; Prasetyo, Danang; Damiasih (CV. Kurnia Grup, 2024)
The tourism sector in Bantul Regency has so far only highlighted ecotourism-based tourist destinations in the form of beaches, pine forests, and sand dunes. Sedayu Karst Tubing is part of an ecotourism-based tourist destination, but the number of visitors is not as many as other ecotourism-based tourist destinations in Bantul Regency. Therefore, enhancing tourist satisfaction is essential to boost the number of visitors to Karst Tubing Sedayu. Thus, this research aims to find out how the facilities and image of tourist destinations influence increasing tourist satisfaction. Researchers used quantitative methods with a comparative causal research type, and this research produced the statement that facilities had an effect on increasing tourist satisfaction, as well as that the image of tourist destinations had an effect on increasing tourist satisfaction. Therefore, we can draw the conclusion that both the facilities and the tourist destination's image significantly influence the increase in tourist satisfaction. However, it would be beneficial if the management and the relevant government collaborated to enhance the quality of the Sedayu Karst Tubing tourist destination. This would foster a greater sense of satisfaction among tourists, thereby potentially increasing the number of visits to Sedayu Karst Tubing, Bantul Regency.